(3GdYOd hGdJhMjO hfaj GdJTHjg Yf Gddg GdhGMO GdMejOs - (3GdbGSe Hf EHQGgje Hf ESeGYjd GdMSfj GdYdhqj, CHh eMeO, GdeYQha HGdQSj , J (B246 (3g` s
(3ChdgG (B:s
(3GdMeO ddg Ydi eG CSZ YdjfG ef fYeI s
(3BNQgG (B:s
(3hPdc Cf GdfhQ hGdXdeI eNdhbGf eMOKGf HhMOGf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfis
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJhMjO hGdedd hGdfMds